Multi‐image encryption algorithm based on image hash, bit‐plane decomposition and dynamic DNA coding - Zhang, Qiuyu; Han, Jitian; Ye, Yutong (IET image processing, 2021)
Problems such as large data volumes, slow transmission rates and low security often occur when transmitting multiple digital images over the internet. In order to protect the content security of multiple images and improve the speed of internet transmission, a multi‐image encryption algorithm based on image hash, bit‐plane decomposition and dynamic DNA coding is proposed in this study. First, the proposed algorithm merges several grey images and image hashing algorithm is used to generate the initial key for chaotic mapping. Second, the random sequence generated by the improved three‐dimensional chaotic map is used to decompose the bit plane of the merged image and the bit‐plane matrix is substituted numerically. Finally, the random sequence generated by the four‐dimensional hyperchaotic system is used to perform dynamic DNA coding and calculation on the image and the final multiple ciphertext images are generated by decomposition of the pixel matrix. The experimental results show that the proposed algorithm has large key space, strong key sensitivity, strong security and robustness, and can resist various conventional attacks such as statistical analysis, differential attack, exhaustive attack, cropping and noise attack.